Economic and Social Development Councils: the experience of Brazil (Revista LIDER, 2020)
Over the last few years the Economic and Social Development Council of Brazil, created by President Lula in 2003, has been in place. This agreement tool was also reproduced at the federal state level. After a decade, what have been its achievements and limits? This paper attempts to answer this question looking through the brazilian historic experience on councils as economic decision structures in the last century and by analyzing the present model of development councils in the national and state level, with special focus on the State of Rio Grande do Sul. The conclusions point toward success in social dialogue but limitations in their representation skills.